When Coke Is Not Hydrating - Mohammed Bahaa Aldeen MD; Nibras Talibmamury MD; Sumer Alalusi MD; Omar Nadham MD; Abdel Rahman Omer MD; Roger D. Smalligan MD (SAGE Publishing, 2014)
A 47-year-old African American man was admitted with 4 days of back pain, nausea and vomiting, and low urine output. There was no history of fever, dysuria, frequency, hesitancy, viral symptoms, trauma, rash, or constipation. Despite his past medical history of hypertension, diabetes mellitus, and hyperlipidemia he denied taking any medications for 18 months, including nonsteroidal anti-inflammatory drugs, acetaminophen, or antacids. He denied smoking and alcohol but admitted to cocaine use. No significant FH. Physical examination results were as follows: BP 235/125 mm Hg, heart rate 90 beats/min, temperature 98°F, O 2 saturation normal; lungs and heart normal, abdomen soft but bilateral costovertebral angle tenderness. Neurological examination was normal. Laboratory tests yielded the following results: creatinine (Cr) 10.5 mg/dL (1.2 mg/dL in 2010), blood urea nitrogen 63 mg/dL, glucose 151 mg/dL, Ca 9.4 mg/dL, PO 4 6.1 mg/dL, Hgb 15 g/dL, white blood cells (WBC) 9100, platelets 167 000, amylase/lipase normal, aspartate aminotransferase/alanine aminotransferase (AST/ALT) normal, bilirubin 1.4 mg/dL, alkaline phosphatase 39 IU/L, creatine phosphokinase 127 µg/L. Hepatic panel, C- and P-ANCA (cytoplasmic- and perinuclear-antineutrophil cytoplasm antibodies, respectively), anti-GBM (anti-glomerular basement membrane), antimyeloperoxidase, antinuclear antibody, and Helicobacter pylori were all negative. C3, C4 normal, urinalysis: 2+ blood, no white blood cells or eosinophils, no casts, no albumin, negative for nitrate/leukocyte esterase and bacteria. Imaging: chest radiograph, abdominal radiograph, computed tomography of the abdomen, electrocardiography, and transthoracic echocardiography were all normal. Course . The patient's urine output declined from 700 to 400 cm 3 /d and the on third day he required hemodialysis with Cr 14 mg/dL. Renal biopsy showed typical findings of interstitial nephritis. The patient was dialyzed for 10 days and responded to steroids and went home with an improving Cr of 3.5 mg/dL, back to baseline of 1.5 in 8 weeks. Discussion . Internists encounter patients with acute kidney injury (AKI) on a daily basis, most of which can be explained by prerenal azotemia, acute tubular necrosis (ATN), obstruction, or rhabdomyolysis among other etiologies. Cocaine is only rarely implicated as an etiology of AKI and if it is, usually the injury is due to ATN or pigment effects. Acute interstitial nephritis (AIN) caused by cocaine, on the other hand, has only been described in a handful of cases. AIN is a renal lesion that causes a decline in creatinine clearance and is characterized by an inflammatory infiltrate in the kidney interstitium and is most often associated with drug therapy. AIN can also be seen in autoimmune disorders like systemic lupus erythematosus, Sjögren's syndrome, or sarcoidosis; or with infections remote to the kidney like Legionella, leptospirosis, and streptococcal disease. Our case was very similar to the other reported cases of AIN due to cocaine in that all have occurred in middle-aged African American males and all have responded to steroids. This case reminds clinicians to consider AIN in patients with AKI and a history of cocaine abuse.